2016
DOI: 10.3402/ejpt.v7.29453
|View full text |Cite
|
Sign up to set email alerts
|

Investigating biological traces of traumatic stress in changing societies: challenges and directions from the ESTSS Task Force on Neurobiology

Abstract: Traumatic stress can have severe consequences for both mental and physical health. Furthermore, both psychological and biological traces of trauma increase as a function of accumulating traumatic experiences. Neurobiological research may aid in limiting the impact of traumatic stress, by leading to advances in preventive and treatment interventions. To promote the possibility for clinical implementation of novel research findings, this brief review describes timely conceptual and methodological challenges and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Moreover, studies conducted in patients diagnosed with personality disorders, depression, 223 psychotic 224 and bipolar disorders 225 show that the spectrum of psychiatric disorders, which are impacted in onset and progression by trauma exposure, is much broader than formally acknowledged as trauma-related. 226…”
Section: The Spectrum Of Psychiatric Disorders Impacted By Trauma Is mentioning
confidence: 99%
“…Moreover, studies conducted in patients diagnosed with personality disorders, depression, 223 psychotic 224 and bipolar disorders 225 show that the spectrum of psychiatric disorders, which are impacted in onset and progression by trauma exposure, is much broader than formally acknowledged as trauma-related. 226…”
Section: The Spectrum Of Psychiatric Disorders Impacted By Trauma Is mentioning
confidence: 99%
“…Although not yet implemented, other treatment innovations include hormonal enhancers (D-cycloserin, cortisol, oxytocin; e.g. Thomaes et al, 2016).…”
Section: Psychotraumatology In the Netherlandsmentioning
confidence: 99%
“…We present the results of the retrieved studies in terms of hypothalamic-pituitary-adrenal (HPA)-axis and endocannabinoid system function, immune reactions, neuroplasticity, novel pharmacological targets, and shortening of telomere length, which confirm a synergistic effect on a neurobiological level between the two entities.Brain Sci. 2020, 10, 173 2 of 15 studies have shown that trauma-related disorders are associated with the dysfunctioning of numerous biological systems, and that PTSD symptom severity exerts a cumulative effect on premature aging of the immune system and telomere length [8].Human functional imaging studies have identified an increased connectivity between the ventromedial prefrontal cortex (vmPFC), locus coeruleus (LC), hypothalamus, hippocampus, basolateral amygdala (BLA), and bed nucleus of the stria terminalis (BNST) in PTSD patients, while more subcortical areas like the periaqueductal gray area (PAG) and central amygdala (CeA) gradually become involved when the severity of a threatening stimulus becomes aggravated [9,10].Before the last decade, the predominant neurobiological model of PTSD concentrated on the pathway of fear conditioning involving mainly the amygdala system [11]. The preparations of the new DSM-5 broadened the criteria to include further emotionally dysregulated states like anger, guilt, shame, and symptoms of derealization and depersonalization, as well as altered self-and other-related conditions and deficits in social cognitions.…”
mentioning
confidence: 99%
“…Brain Sci. 2020, 10, 173 2 of 15 studies have shown that trauma-related disorders are associated with the dysfunctioning of numerous biological systems, and that PTSD symptom severity exerts a cumulative effect on premature aging of the immune system and telomere length [8].…”
mentioning
confidence: 99%